Bioavailability and Biokinetics of Anthocyanins From Red Grape Juice and Red Wine. Issue 5 (1st December 2004) - Bitsch, Roland; Netzel, Michael; Frank, Thomas; Strass, Gabriele; Bitsch, Irmgard
Abstract : In a comparative study, 9 healthy volunteers ingested a single oral dose of 400 mL red grape juice or red wine with dose-adjusted anthocyanin content (283.5 mg or279.6 mg, resp.) in crossover. The content of anthocyanin glucosides was detected in plasma and urinary excretion. Additionally, the plasmatic antioxidant activity was assessed after intake. Based on the plasma content, biokinetic criteria of the single anthocyanins were calculated, such as AUC, c max, t max, and the elimination ratet 1 / 2 . The urinary excretion of total anthocyanins differed significantly and amounted to0.18 % (red wine) and0.23 % (red grape juice) of the administered dose. Additionally, the plasmatic antioxidant activity increased to higher levels after juice ingestion compared to wine. The intestinal absorption of the anthocyanins of red grape juice seemed to be improved compared to red wine, suggesting a possible synergistic effect of the glucose content of the juice. The improved absorption resulted in an enhanced plasmatic bioactivity.